2005
DOI: 10.1002/jsfa.2209
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol glycosides and antioxidant capacity of various blackberry and blueberry genotypes determined by high‐performance liquid chromatography/mass spectrometry

Abstract: Flavonol glycoside composition and content in blueberry and blackberry extracts were determined using a high-performance liquid chromatographic (HPLC) separation method coupled with photodiode array (PDA) and mass spectrometric (MS) detection. The hydrophilic antioxidant capacities of crude and fractionated flavonol extracts were also determined by the oxygen radical-absorbing capacity (ORAC FL ) and photochemiluminescence (PCL) assays. Eight flavonols of quercetin and quercetin-sugar conjugates were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
88
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 36 publications
20
88
2
3
Order By: Relevance
“…These results are in agreement with those of Cho et al (2005), who found a correlation coefficient of r 2 = 0.72, when using the oxygen radical-absorbing capacity (DRAC) method, and r 2 = 0.88 when using the photochemiluminescence assay method. These authors reported that several types of phenolics in the fresh extracts varied in their ability to scavenge peroxyl and superoxide anion radicals.…”
Section: Antioxidant Capacitysupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with those of Cho et al (2005), who found a correlation coefficient of r 2 = 0.72, when using the oxygen radical-absorbing capacity (DRAC) method, and r 2 = 0.88 when using the photochemiluminescence assay method. These authors reported that several types of phenolics in the fresh extracts varied in their ability to scavenge peroxyl and superoxide anion radicals.…”
Section: Antioxidant Capacitysupporting
confidence: 91%
“…This agrees with Wang et al (2008), who reported that cyanidin-3-glucoside is the prevalent anthocyanin and responsible for the AC in blackberries. Similarly, six blackberry genotypes analyzed by Cho et al (2005) showed that distribution of cyanidin aglycones in each cultivar ranged from 75 to 84% for cyanidin 3-glucoside, from 1 to 12% for cyanidin 3-rutinoside, from 4 to 8% for cyanidin 3-dioxaloyglucoside, from 3 to 8% for cyanidin 3-dioxaloylglucoside, and from 2 to 3% for cyanidin 3-(malonyl) glucoside. Dther anthocyanins were identified as delfinidin-3-glucoside (between 41.86 and 49.26 mg kg -1 fw), malvinidin-3-glucoside (2.96 to 56.45 mg kg -1 fw).…”
Section: Individual Polyphenol and Anthocyanin Contentmentioning
confidence: 96%
“…Literatürde üzümsü meyve tüketiminin insan sağlığına olumlu katkılarının olduğunu gösteren çalışmalar mevcuttur [2]. Yaban mersini fenolik bileşenlerce, özellikle antosiyaninlerce zengindir [3] ve birçok diğer meyve ve sebzeye göre antioksidan kapasitesi oldukça yüksektir. Fakat onları değerli kılan fenolik bileşenleri genellikle; ısı, ışık, nem, yüksek sıcaklık ve oksijen gibi olumsuz çevresel faktörlere karşı hassas bileşenlerdir.…”
Section: Introductionunclassified
“…In this case, the compound identities were assigned by also considering the fragmentation pattern described by Scoparo 23 , as well as on the basis of the elution order. The first compound eluted (peak 15) was tentatively assigned as quercetin-galloylgalactoside, while the second peak eluted was assigned as quercetin-galloylglucoside (peak 16); both compounds have previously been detected in blueberries 24 . The myricetin derivatives included one rutinoside, one hexoside, one pentoside, one galloylhexoside, and one unidentified derivative.…”
Section: Flavonolsmentioning
confidence: 91%